Family‐centred care: a qualitative study of Chinese and South Asian immigrant parents' experiences of care in paediatric oncology. Issue 2 (9th November 2011) - Watt, L.; Dix, D.; Gulati, S.; Sung, L.; Klaassen, R. J.; Shaw, N. T.; Klassen, A. F.
Abstract Background Over the past two decades, there is increasing emphasis being placed upon providing family‐centred care (FCC) in paediatric oncology settings. However, there is a lack of knowledge of FCC in paediatric oncology from the perspectives of immigrant parents. The purpose of this paper is to describe Chinese and South Asian immigrant parents' experiences of FCC in paediatric oncology settings in Canada. Methods This study adopted a constructivist grounded theory approach. Fifty first generation Chinese and South Asian parents of children with cancer who were at least 6 months post‐diagnosis were recruited from six Canadian paediatric oncology centres. Interviews were conducted in English, Cantonese, Mandarin, Urdu, Punjabi or Hindi, and transcribed into English. Analysis involved line‐by‐line, focused and theoretical coding, and the use of the constant comparison method. Results Findings indicated that overall parents were highly satisfied with the care and services they received, and their experiences were reflective of the key elements of FCC. However, there were some areas of concern identified by participants: parents not perceiving themselves as a member of the medical team; inconsistency in the quality and co‐ordination of services among healthcare providers; disrespectful and mechanical manner of a few healthcare providers; and parents' discomfort with healthcare providers communicating sensitive health‐related information directly with their child. Conclusions In order to successfully provide family‐centred services to immigrant parents of children with cancer, better communication of the elements of FCC between healthcare staff and families is needed to negotiate a clear role for the parents as partners of the healthcare team. Moreover, a better understanding of how family relationships are structured in immigrant families will assist healthcare providers to balance the best interests of the child with that of the family as a unit.